Inferior alveolar nerve transection disturbs innate immune responses and bone healing after tooth extraction. Issue 1 (16th May 2019) - Xu, Yamei; Xia, Mengnan; Chen, Tao; Yang, Yao; Fu, Gang; Ji, Ping; Wu, Qingqing
Abstract: Coordination between the nervous and innate immune systems to maintain bone homeostasis is largely uncharacterized. The present study investigated the sensory–immune interaction in resting alveolar bone and healing socket by surgical sensory denervation. Bone histomorphometry and immunohistochemistry showed that sensory denervation resulted in moderate suppression of bone remodeling, with a proinflammatory milieu manifested by increased neutrophil recruitment and possible alternations in macrophage phenotypes along the resting bone surface. This denervation effect intensified when bone remodeling was triggered by tooth extraction, as revealed by disrupted temporospatial variations in macrophage subpopulations and neutrophil infiltration, which were closely associated with a dramatic decline in socket bone filling and residual ridge height. Antagonism of calcitonin gene‐related peptide (CGRP) brought about similar antianabolic and proinflammatory effects as sensory denervation, suggesting that sensory nerves may monitor the bony milieu by CGRP. Depletion of macrophages, rather than neutrophils, ruled out CGRP effects, illustrating that macrophages were the primary immune mechanism that linked sensory innervation, innate immunity, and bone. The data support that sensory innervation is required for control of innate immune responses and maintenance of bone homeostasis. Sensory neuropeptides, such as CGRP, are a possible target for the development of proanabolic treatments in bone disease by modulating innate immune responses. Abstract : The present study investigated the sensory–immune interaction in resting alveolar bone and healing socket by surgical sensory denervation. Bone histomorphometry and immunohistochemistry showed that sensory denervation resulted in moderate suppression of bone remodeling, with a proinflammatory milieu manifested by increased neutrophil recruitment and possible alternations in macrophage phenotypes along the resting bone surface.